Advancements in Radiotherapy: Precision Techniques for Enhanced Tumor Targeting - hadi, Doaa mohammed; Mustafa, Ahmed Rabie Jaber; Mohsen, Ali Karim; sada, Hussein Kadhim Abdel; Katea, Ali Mardan (American Journal of Botany and Bioengineering, 2024)
Cancer incidence continues to surge globally, with an estimated 21.96 million cases and 10.05 million deaths in 2018. Cancer is currently the second leading cause of death and is responsible for an estimated 1 in 6 deaths worldwide. Oncology, through a combination of procedures such as surgery, chemotherapy, radiotherapy, immunotherapy, hormonal therapy, and more, provides treatment to patients diagnosed with malignancies. Radiotherapy as a treatment modality has become increasingly successful in recent decades. Radiotherapy alone or in combination with palliative or curative intent is commonly used in around 50 percent of cancer cases. Although numerous breakthroughs have improved patient outcomes worldwide, intense side effects are often associated with all common cancer treatments. Among the diverse treatment options available for cancer, radiotherapy stands out as an essential tool for both palliative and curative management. As part of a multidisciplinary approach to cancer management, the clinical practice of radiotherapy has evolved over the years. Until the last decade, cancer centers transformed from moderate-sized facilities focused on large fields and simple techniques to being megacenters at the forefront of cutting-edge technology, which can deliver pinpoint treatments with sub-millimeter precision. The learning curve for radiation oncologists is steep, given the fact that cancer care is a large and rapidly expanding area requiring a strong knowledge of clinical oncology, radiation biology, medical physics, and radiobiology. Traditional radiotherapy techniques to advance tumor conformation and reduce the dose to normal tissue are also being replaced by different precise and targeted techniques.